The Criminalization Of Cohabiting Policy In The Revision Of Criminal Law In Indonesia - Baktiar Atmadi (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2019)
Cohabiting seen as acts that violate the values of decency. But in the Criminal Code, this act is not a criminal offense. For related research needs to be undertaken efforts to criminalize the cohabiting as criminal law reform in Indonesia. The purpose of this study was to analyze: the reasons for cohabiting in Indonesia, the basic consideration of the need for the criminalization of cohabiting in criminal law reform in Indonesia and the criminalization of cohabiting policy in the revision of criminal law in Indonesia in the future. The method used is normative, then the data was analyzed using the Theory of Law Enforcement and Justice Theory of Pancasila. The study concluded that: 1) The reasons for cohabiting in Indonesia are less prepared mentally, economic, traumatic experience, weak monitoring social control in society, Wedding paradigm shift and the notion of sex is a private person's rights as well as the weakness of Indonesian law. 2) Rationale and criminalization of cohabiting consideration, based on: Socio-Philosophical Basis and Socio Cultural National Legal Systems, Platform Values Decency / National Agreement and Platform for Research and Comparative Studies. 3) The policy of criminalization cohabiting in the positive law in Indonesia in the future necessary to maintain it being understood obscenity, to reduce and prevent acts of vigilantism by the community and for the unification of customary law governing cohabitation. Keywords: Criminalization Policy; Cohabiting; Indonesia Criminal Law.